2020
DOI: 10.3390/w12030676
|View full text |Cite
|
Sign up to set email alerts
|

Legionellosis and Recent Advances in Technologies for Legionella Control in Premise Plumbing Systems: A Review

Abstract: This review discusses Legionella, among the most prolific and publicly well-known waterborne pathogens, and advances in potential treatment technologies. The number of cases associated with Legionella continues to rise, as does its public awareness. Currently, cases associated with premise plumbing account for the largest number of legionellosis cases in the United States. So, while it is important to understand Legionella as such, it is also important to investigate how to treat drinking water in premise plum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 100 publications
(208 reference statements)
0
24
0
Order By: Relevance
“…As such, several works have investigated the effect of different control measures (conventional and new) on Legionella prevalence in real-field systems. Conventional approaches include disinfectant dose, temperature control, or water flushing [85]. Under this topic, most of the published studies are focused on hot water networks, probably because there is only a restricted number of control measures available, and these should fulfill the requirements of drinking water regulations (which limit, for example, the type of biocides to use), as well as comply with safety measures for users (e.g., avoid scalding).…”
Section: Microbial Control Strategiesmentioning
confidence: 99%
“…As such, several works have investigated the effect of different control measures (conventional and new) on Legionella prevalence in real-field systems. Conventional approaches include disinfectant dose, temperature control, or water flushing [85]. Under this topic, most of the published studies are focused on hot water networks, probably because there is only a restricted number of control measures available, and these should fulfill the requirements of drinking water regulations (which limit, for example, the type of biocides to use), as well as comply with safety measures for users (e.g., avoid scalding).…”
Section: Microbial Control Strategiesmentioning
confidence: 99%
“…However, all cases, clusters, or outbreaks are linked to artificial freshwater environments, which represent a main reservoir of Legionella and a significant health risk from an epidemiological point of view since the main vehicle of microorganism diffusion and exposure to humans is the aerosol produced by some devices, such as condensers, showers, faucets, humidifiers, whirlpool baths, and medication nebulizer devices (Hines et al, 2014;Mercante and Winchell, 2015;Carlson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many hot water system configurations require large tank sizes in open-loop systems that provide increased system volumes and water ages. Water-efficient fixtures also significantly reduce flow and therefore demand [15]. For example, an inefficient showerhead can use between 15 and 25 L of water per minute, while an efficient showerhead can use between 6 and 8 L of water per minute.…”
Section: Leadership In Energy and Environmentalmentioning
confidence: 99%
“…In general, superheat-and-flush should only be implemented as a component for the short-term management of premise plumbing pathogens, since it can cause infrastructure damage, does not prevent re-seeding, and can exacerbate other water quality issue including tastes and odours. For example, several studies have observed recolonisation by Legionella within weeks to months after treatment [15,43,151]. Temmerman et al [152] also demonstrated the ability of Legionella pneumophila to rapidly proliferate after temperatures were lowered and suggested this was a microbial response to nutrients released by newly killed biofilm.…”
Section: Temperature Controlmentioning
confidence: 99%
See 1 more Smart Citation